PREVALENCE OF CARDIOVASCULAR RISK FACTORS IN HOSPITALIZED PATIENTS IN A LIMA HOSPITAL - Zuni Chavez, Karla X. (2019)
Objective: To determine the factors associated with cardiovascular risk in patients of the HSEB Department of Medicine. Methods: Prospective, cross-sectional, descriptive and observational study, included 83 probabilistically chosen patients from a universe of 105 hospitalized from the HSEB Department of Medicine. For the calculation, OpenEpi version 3 and Microsoft Excel 2010 were used and in the analysis and interpretation of the data, graphs and tables of relative and absolute frequencies were used. Results:53% were women and the average age was 54.5 years. The frequency of main risk factors was: Overweight 30.1%, obesity 13.3%, the Ci / Ca index very high in women 54.2%, family history of AMI 38.5% and HTA 34.6%, DM2 65.5%, High Cholesterol 34.4% , HTA 21.7% of these 73.9% were controlled, classified and were optimal 21.7% and Normal-High 34.8, also sedentary lifestyle 50%, carbohydrate consumption 56.6%, lipids 32.5%, fast food 44.6% and as a degree of Anxiety less than 54.2% and greater than 32.5%. Conclusion:There is a higher risk of a coronary event more in women over 50 years of age than in men, having as main cardiovascular risk factors diet, sedentary lifestyle, overweight, normal-high pressures, minor anxiety, andcomorbidities Associated such as diabetes and high cholesterol.